MODERNISASI PENDIDIKAN ISLAM DI TIMUR TENGAH - Habibi, Debi Fajrin (Risâlah, Jurnal Pendidikan dan Studi Islam, 2018)
Abstract The essence of Islamic education is to abolish the dualism of religious knowledge and general knowledge. The Middle East as a model for the Islamic world especially in Islamic thought and education seeks to reunite the concept of integration of both knowledge. Westernized modernization has implications for the changing concept of education in the Middle East. This article attempts to describe socio-historically, the modernization of Islamic education taking place in the Middle East. Egypt and Turkey became the two countries used as a model to change the concept of Islamic education towards progress. Geographically Egypt became the hub of Arab and African culture, while Turkey was at the meeting line of Arab and European cultures. Egypt with the spirit of scientific integration and Turkey that echoes secularism both carry a term that is modernization.